Prevalensi Nyeri Kepala pada Mahasiswa Keperawatan Anestesiologi - Ningsih, Santi Wiwitia; Burhan, Asmat; Yanti, Linda (FORIKES, 2025)
Headaches in college students can be caused by stress arising from high study loads, tight assignment deadlines, and increasingly complex academic demands. Emotional increases can trigger headaches. Primary headaches can impact adult students in education, thus affecting engagement in activities and academic achievement. The purpose of this study was to determine the prevalence of headaches in anesthesiology nursing students. This study used a quantitative descriptive method, involving 123 students selected using a simple random sampling technique. Data were collected using the Headache Screening Questionnaire-Dutch Version (HSQ-DV) questionnaire and analyzed descriptively in the form of frequencies and proportions. The results showed that the most common type of headache was Tension-Type Headache (TTH) with a prevalence of 23.6% (probable TTH) and 3.3% (TTH). Meanwhile, the prevalence of migraine was recorded at 8.9% (probable migraine) and 1.6% (migraine). Meanwhile, headaches were more often experienced by women aged 17-25 years, with a frequency of 1-4 headaches once a month. It was further concluded that tension-type headaches (TTH) are more common among anesthesiology nursing students, especially females. Improved academic stress management, such as psychological interventions and health education, can prevent negative impacts on students and support academic success.Keywords: headache; students; anesthesiology nursing; tension-type headache ABSTRAK Nyeri kepala pada mahasiswa dapat disebabkan oleh stress yang timbul akibat beban studi yang tinggi, tenggat waktu tugas yang ketat, serta tuntutan akademik yang semakin kompleks. Peningkatan emosional dapat memicu nyeri kepala. Nyeri kepala primer dapat berdampak pada mahasiswa dewasa yang sedang dalam pendidikan, sehingga dapat memengaruhi keterlibatan dalam aktivitas dan prestasi akademik. Tujuan penelitian ini adalah mengetahui prevalensi nyeri kepala pada mahasiswa keperawatan anestesiologi. Penelitian ini menggunakan metode deskriptif kuantitatif, yang melibatkan 123 mahasiswa yang dipilih dengan teknik simple random sampling. Data dikumpulkan menggunakan kuesioner Headache Screening Questionnaire-Dutch Version (HSQ-DV) dan dianalisis secara deskriptif berupa frekuensi dan proporsi. Hasil penelitian menunjukkan bahwa jenis nyeri kepala yang paling sering ditemukan adalah Tension-Type Headache (TTH) dengan prevalensi 23,6% (probable TTH) dan 3,3% (TTH). Sementara itu, prevalensi migrain tercatat sebesar 8,9% (probable migrain) dan 1,6% (migrain). Sedangkan, nyeri kepala lebih sering dialami oleh perempuan usia 17-25 tahun, dengan frekuensi nyeri kepala 1-4 sekali sebulan. Selanjutnya disimpulkan bahwa nyeri kepala TTH lebih sering dialami oleh mahasiswa keperawatan anestesiologi, terutama perempuan. Pengelolaan stress akademik yang lebih baik, seperti intervensi psikologi dan edukasi kesehatan, untuk mencegah dampak negatif pada mahasiswa dan mendukung keberhasilan akademik.Kata kunci: nyeri kepala; mahasiswa; keperawatan anestesiologi; tension-type headache